Process modeling and simulation for chemical engineers : theory and practice - Upreti, Simant Ranjan (Chichester, UK ; Hoboken, NJ : John Wiley & Sons, 2017)
This book provides a rigorous treatment of the fundamental concepts and techniques involved in process modeling and simulation. The book allows the reader to: (i) Get a solid grasp of "under-the-hood" mathematical results (ii) Develop models of sophisticated processes (iii) Transform models to different geometries and domains as appropriate (iv) Utilize various model simplification techniques (v) Learn simple and effective computational methods for model simulation (vi) Intensify the effectiveness of their research Modeling and Simulation for Chemical Engineers: Theory and Practice begins with an introduction to the terminology of process modeling and simulation. Chapters 2 and 3 cover fundamental and constitutive relations, while Chapter 4 on model formulation builds on these relations. Chapters 5 and 6 introduce the advanced techniques of model transformation and simplification. Chapter 7 deals with model simulation, and the final chapter reviews important mathematical concepts. Presented in a methodical, systematic way, this book is suitable as a self-study guide or as a graduate reference, and includes examples, schematics and diagrams to enrich understanding. End of chapter problems (with solutions and computer software available online) are designed to further stimulate readers to apply the newly-learned concepts. End of chapter problems (with solutions and computer software available online ) are designed to further stimulate readers to apply the newly learned concepts.
Fundamental relations -- Constitutive relations -- Model formulation -- Model transformation -- Model simplification and approximation -- Process simulation -- Mathematical review.
Includes bibliographical references and index.
Print version record.
Keywords: Chemical processes -- Mathematical models; Chemical processes -- Data processing; Chemical processes -- Data processing; Chemical processes -- Mathematical models; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Electronic books